UPAYA MENINGKATAN KEMAMPUAN GURU SD MENGELOLA LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR MELALUI DISKUSI KELOMPOK GURU - Heri Rusyani (UNIVERSITAS BENGKULU, 2016)
This study aimed to describe the process of managing the environment as a source of learning through discussion groups of teachers in primary schools 03 Lebong Atas. After beinggiven the action on the implementation of the research, there is an increased ability of teachers to manage the natural surroundings as a learning resource. In detail, the acquisition value of the average increase in the ability of teachers to manage the natural surroundings as a learning resource that is the average value of the observation results of the discussions in the first cycle of 66 to 85 in the second cycle there is an increase of 19%, the scenario exercise instructional averagevalue of 73.13 in the first cycle to 93.75 in the second cycle there was an increase 20.62 %, learning activities or in the process of learning the average value of 72.88 in sklus I to 95 in the second cycle, there is a 22.12 % increase.Keywords : ability , teacher , environment , learning resources